Answer:
3x^2 +8x +3
Step-by-step explanation:
(6x^2 + 8x - 3) - (3x^2 - 6)
Distribute the minus sign
(6x^2 + 8x - 3) - 3x^2 + 6
Combine like terms
3x^2 +8x +3
Answer:
![\boxed{ \bold{ \huge{ \boxed{ \sf{ - 2x + 28}}}}}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Cbold%7B%20%5Chuge%7B%20%5Cboxed%7B%20%5Csf%7B%20-%202x%20%2B%2028%7D%7D%7D%7D%7D)
Step-by-step explanation:
![\sf{2x + 4(7 - x)}](https://tex.z-dn.net/?f=%20%5Csf%7B2x%20%2B%204%287%20-%20x%29%7D)
Distribute 4 through the parentheses
![\dashrightarrow{ \sf{2x + 28 - 4x}}](https://tex.z-dn.net/?f=%20%5Cdashrightarrow%7B%20%5Csf%7B2x%20%2B%2028%20-%204x%7D%7D)
Collect like terms
![\dashrightarrow{ \sf{2x - 4x + 28}}](https://tex.z-dn.net/?f=%20%5Cdashrightarrow%7B%20%5Csf%7B2x%20-%204x%20%2B%2028%7D%7D)
![\dashrightarrow{ \sf{ - 2x + 28}}](https://tex.z-dn.net/?f=%20%5Cdashrightarrow%7B%20%5Csf%7B%20-%202x%20%2B%2028%7D%7D)
Hope I helped!
Best regards! :D
Answer:
Exercise 1:
base [b]=8cm
perpendicular [p]=6cm
hypotenuse [h]=?
<u>By</u><u> </u><u>using</u><u> </u><u>Pythagoras</u><u> </u><u>law</u>
h²=p²+b²
h²=6²+8²
h=√100
h=10cm
<u>So</u><u> </u><u>another</u><u> </u><u>side's</u><u> </u><u>length</u><u> </u><u>is</u><u> </u><u>1</u><u>0</u><u>c</u><u>m</u>
<u>Exercise</u><u> </u><u>2</u><u>:</u>
base [b]=6m
perpendicular [p]=bm
hypotenuse [h]=8m
By using Pythagoras law
h²=p²+b²
8²=b²+6²
b²=8²-6²
b=√28=2√7 0r 5.29 or 5.3
So height of kite is√<u>28</u><u>o</u><u>r</u><u> </u><u>2√7 0r 5.29 or 5.3 m</u>
Step-by-step explanation:
[Note: thanks for translating]
1:40 because if we think of this just like a fraction
![\frac{3}{120}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B120%7D%20)
that simplifys down to
![\frac{1}{40}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B40%7D%20)
and because fraction simplifications are similar (related to each other) we can concur that these would be too.
Enjoy!=)
Answer:
A
Step-by-step explanation: